Development Of E-Komatik Media (Mathematical E-Comic) With A Contextual Approach To The Material Of Rectangles And Triangles - Ani Afifah; Putri, A.D. (Jurnal Scientia, 2021)
Media can help the learning process, its existence is expected to improve student understanding. This study aims to develop an E-Komatik (Mathematical E-Comic) media with a contextual approach to the material of quadrilaterals and triangles to build the understanding of the seventh grade junior high school students. The development model used by the Thiagarajan model known as the 4-D model (four-D model) was modified into a 3-D model which only reached the third stage, namely define, design stage, and develop stage, because it was adapted to the needs of learning media development. The media development process uses Inkscape for coloring and finishing comics. The subject of the trial used sampling by taking 10 students seen from the level of student ability. The results showed that E-Komatik was valid based on the validation assessment, effective based on the percentage of learning completeness and practicality from the results of implementation observations. In addition, E-Komatik can also help students' understanding based on 3 levels, namely 41% at the intrapolation level, 35% at the translational level, and 24% at the extrapolation level.